Cold induced pseudoneutropenia in human immunodeficiency virus infection: first case report and review of related articles - Prashant Goyal; Dipti Agrawal; Jitender Kailash; Sompal Singh (Mediterranean Journal of Hematology and Infectious Diseases)
Cold agglutination of erythrocyte or platelet aggregation in vitro due to cold agglutination are well recognized and extensively studied. Aggregation of leucocyte is a rare hematological phenomenon resulting in a spurious low leucocyte count performed using automated hematology analyzers. Aggregation of leucocyte may relate to malignancy, lymphoproliferative disorders, infection, liver diseases, or autoimmune disorders. It is believed that the mechanism of leucocyte aggregation is mainly related to the use of EDTA (ethylene diamine tetraacetic acid) anticoagulant or is temperature-mediated. Leucoagglutination is associated with either a spurious leucopenia or an underestimation of leucocytosis. This can adversely affect management decisions in terms of unnecessary management of leucopenia or ignoring a leucocytosis that may be indicator of an underlying serious disease. To our knowledge, we report here for the first time the occurrence of pseudoneutropenia due to temperature-mediated, EDTA-independent neutrophil agglutination in adult with human immunodeficiency virus (HIV) infection.